Treating clinically significant avoidance of public transport following the London bombings? - Handley, R; Salkovskis, P; Ehlers, A (2009)
BACKGROUND: The present paper describes the cognitive-behavioural approach evolved and adapted to treat survivors of the London bombings experiencing fear and avoidance of public transport (travel phobia). METHOD: Treatment outcomes for a consecutive case series (N = 11) are reported. RESULTS: All individuals who completed treatment (N = 10) had returned to their pre-bombing use of transport and reported minimal symptoms. CONCLUSIONS: The need for appropriately tailored treatment based on differential diagnosis and formulation and the importance of incorporating skills for treatment of posttraumatic stress disorder are discussed.